ON THE REAL-WORLD-SEMANTICS INTERPRETABILITY OF FUZZY RULE BASED SYSTEMS UNDER FUZZY SET APPROACH AND HEDGE ALGEBRA APPROACH - Anh, Nguyen Thu; Ho, Nguyen Cat (Journal of Computer Science and Cybernetics, 2017)
The study will further discuss the novel real-world-semantics-based approach (RWS-approach) to the interpretability of fuzzy systems proposed in [15] to show that the RWS-interpretability of fuzzy systems in this approach is very essential and practical. It is also analyzed that the usual theories in the mathematics and the physics are all RWS-interpretable or, roughly speaking, this means that they are able to model their real-world parts, properly. It is pointed out that though the fuzzy set theory is a great one which is very flexible, has many advantages in the application and obtains numerous achievements, methodologically, it still has an essential shortcoming that it is not RWS-interpretable on the viewpoint of this RWS-approach. To ensure the RWS-interpretability of a fuzzy linguistic system, it is argued that word-domains of variables with their own order-based semantics should be made use and interpreted as a formal bridge to connect the real-world semantics with the constructed fuzzy linguistic system that works on the designed computational semantics of linguistic words. It is initially shown that there exists a formalism based on the theory of hedge algebras to design RWS-interpretable fuzzy systems.